(untitled) (International Journal of Engineering and Computer Science, 2017)
Text passwords have been adopted as the primary mean for user authentication in online websites. Humans are not experts in memorizing them, therefore they rely on the weak passwords. As they are the static passwords there are some adversary who can launch attacks to steal passwords, and suffers quitely from few security drawbacks: phishing, keyloggers and malware. This problem can be overcome by a protocol named oPass which leverages a user’s cellphone and an SMS to thwart password stealing. Opass greatly avoids the man-in-middle attacks. In case of users lose their cellphones, this still works by reissuing the SIM cards and long-term passwords. This is a efficient user authentication protocol and is at affordable cost